Pemanfaatan Fly Ash dan Alkali Resistant Glass Fibre (ARG) dalam Pembuatan Paving Block - Soebandono, Bagus (Semesta Teknika, 2013)
The paving block is an alternative to the use of pavement layer that is safe, strong and easy to installation and maintenance. Pavement paving block also can be produced both mechanically and manually. The added fly ash was a waste material from coal combustion in the steam power plant furnace in the form of fine, round, pozzolanic and fibre-resistant. Alkali Resistant Glass Fibre (ARG) which is shaped like a rope 18-36 mm long was added into the paving block with mixed compositions 1 Pc:10 Ps that aims to strengthen the compressive strength and flexibility of the paving block. This research was used 15 samples with mixture variation of fly ash 19% and fiber 0,25%, 0,5%, 0,75% and 1%. Based on the results of laboratory analysis, paving block (1 Pc: 10 Ps) with the addition of fly ash 19% and ARG 0.6% yielding a maximum compressive strength of 18.35 MPa. The addition of fibres with fly ash mixture was also able to increase the compressive strength of the paving block.